Limits of the secular: social experience and cultural memory - Roy, Kaustuv (Palgrave Macmillan, 2017)
This book facilitates a missing dialogue between the secular and the transsecular dimensions of human existence. It explores two kinds of limits of the secular: the inadequacies of its assumptions with respect to the total being of the human, and how it curbs the ontological sensibilities of the human. Kaustuv Roy argues that since secular reason of modernity can only represent the empirical dimension of existence, humans are forced to privatize the non-empirical dimension of being. It is therefore absent from the social, imaginary, as well as public discourse. This one-sidedness is the root cause of many of the ills facing modernity. Roy contends that a bridge-consciousness that praxeologically relates the secular and the non-secular domains of experience is the need of the hour